The Shanhaijing and the origins of daoist sacred geography - Gesterkamp, Lennert (Journal of Daoist Studies, 2021)
The Shanhai jing (Classic of Mountains and Seas) is a description of the sacred geography of early China. This study argues that the later Daoist sacred geography of sacred mountains and grotto-heavens is a continuation and elaboration of the one envisioned in the Shanhai jing. After analyzing the structure, contents, compilation history, and dates of this complex text, I argue that the Shanhai jing originally was intended as a guidebook for administrating resources and territorial relations at the Qin and early Han courts, and followed a specific cosmological model similar to that found in early Daoist texts. The cosmological model of the Shanhai jing stands in opposition to that promoted in the Yugong (Tribute of Yu), a text on geography in the Confucian classics. The study further argues that Daoist sacred geography after the Han continues the cosmological ideals of the Shanhai jing but without the original administrative purposes. Yet it continues its important task of maintaining territorial relations indirectly—through rituals at sacred sites.
Created from Fastlane, Scopus look-up